The Implementation of Ethnomathematics Based-Learning for Students - Cahya Sari Putra, Eka; Nur Mahmudah, Fitri (SJME (Supremum Journal of Mathematics Education), 2021)
The purpose of this study was to find out about ethnomatematics learning among students majoring in mathematics education at Yogyakarta State University, as well as to what extent students' understanding, especially in applying ethno-mathematics in a learning process in the classroom. This study used a qualitative approach with the type of case study, the object of research was one class of mathematics education students at Yogyakarta State University consisting of 31 students. The results of the study provide information that students understand ethnomatematics but are still constrained by the implementation of learning. Students are constrained in preparing lesson plans and teaching materials where they are still unable to integrate cultural material into the mathematics material.